2019
DOI: 10.3389/fcimb.2019.00042
|View full text |Cite
|
Sign up to set email alerts
|

How Viral and Intracellular Bacterial Pathogens Reprogram the Metabolism of Host Cells to Allow Their Intracellular Replication

Abstract: Viruses and intracellular bacterial pathogens (IBPs) have in common the need of suitable host cells for efficient replication and proliferation during infection. In human infections, the cell types which both groups of pathogens are using as hosts are indeed quite similar and include phagocytic immune cells, especially monocytes/macrophages (MOs/MPs) and dendritic cells (DCs), as well as nonprofessional phagocytes, like epithelial cells, fibroblasts and endothelial cells. These terminally differentiated cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 391 publications
(454 reference statements)
3
145
0
Order By: Relevance
“…In aquatic invertebrates, poly (I:C) and viral infections enhanced energy requirements (Li et al ., ; Saray et al ., ). These results revealed that poly (I:C) induces Warburg‐like metabolic effects in treated fish, similar to the conditions observed during intracellular viral replication (Eisenreich et al ., ). These results are consistent with those observed at the transcript level, as pro‐inflammatory ifnγ ‐driven immune cell differentiation (Langevin et al ., ) requires elevated energy (Fritsch & Weichhart, ) for several biochemical processes to enhance immunity.…”
Section: Discussionmentioning
confidence: 97%
“…In aquatic invertebrates, poly (I:C) and viral infections enhanced energy requirements (Li et al ., ; Saray et al ., ). These results revealed that poly (I:C) induces Warburg‐like metabolic effects in treated fish, similar to the conditions observed during intracellular viral replication (Eisenreich et al ., ). These results are consistent with those observed at the transcript level, as pro‐inflammatory ifnγ ‐driven immune cell differentiation (Langevin et al ., ) requires elevated energy (Fritsch & Weichhart, ) for several biochemical processes to enhance immunity.…”
Section: Discussionmentioning
confidence: 97%
“…Many viruses induce host cell death, by apoptosis or pyroptosis among others [37], probably to enhance replication and expansion into the entire organism [38]. For example, HIV-1 activates pathways causing CD4 T-cell death in infected hosts due to caspase-1-mediated pyroptosis triggered by abortive viral infection.…”
Section: Which Consists Of Virus Adhesion Adsorption Entry and Invamentioning
confidence: 99%
“…Due to their involvement in essential cellular processes, mitochondria represent attractive targets for viral and bacterial pathogens (9)(10)(11)(12). Indeed, many pathogenic bacteria were previously shown to modulate mitochondrial dynamics to create the ideal conditions for intracellular replication, immune evasion, and persistence (11,(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%